Oral health related quality of life in Indonesian middle-aged and elderly women (Faculty of Medicine Universitas Indonesia, 2011)
Background: To assess oral health-related quality of life in Indonesian middle-aged and elderly women. Middle–aged women between 45-59 years old were included in this study, because this stage of life is important to prepare them entering the old age. Prevention could be done earlier in order to achieve optimum quality of life for the elderly. The purpose of writing this paper is to inform the policy maker to develop a framework in oral health prevention. Method: Cross-sectional study was done at East Bekasi district, West Java on 236 women 45-82 years of age. Measurement of health related quality of life was performed using the Oral Health-Related Quality of Life (OHRQoL) questionnaire. This questionnaire has already been translated to Indonesian language and has already been validated. Result: About 86.4% of subjects had a good oral health-related quality of life. Number of missing teeth and oral health-related quality of life have a weak correlation (correlation coeffi cient= -0.133, P= 0.041). Conclusion: Oral health-related quality of life did not depend on the number of missing teeth. These fi ndings may have implication for promoting education to middle-aged and elderly women in Indonesia about the importance of oral health.This policy frame work will be recommended to be implemented in hospitals, clinics, community care and institutional care. (Med J Indones 2011; 20:62-5) Keywords: chewimg difficulties, number of missing teeth, tooth ache